Inclusion of glutamine associated with glutamic acid in the diet of piglets weaned at 21 days of age - Teixeira,Alexandre de Oliveira (2014)
The effects of dietary inclusion levels of the association of glutamine with glutamic acid (AminoGut: AmG) on the performance, gastrointestinal morphophysiology, and diarrhea incidence of piglets weaned at 21 days of age were evaluated. In the experiment, 120 piglets with 6.24 ± 1.00 kg initial weight were distributed according to a randomized block experimental design into five treatments with six replicates of four animals each. The following treatments were applied: negative control diet (0% AmG); 0.5% AmG; 1.0% AmG; 1.5% AmG; positive control diet (0% AmG, 4% inclusion of porcine plasma). The inclusion of 1.0% AmG, as compared to the positive control diet, improved weight gain, feed intake and feed conversion ratio. The lowest diarrhea score was observed when 1.0% AmG was included, whereas the best villus height and villus:crypt ratio were obtained with the inclusion of 0.82% AmG. Villus height, crypt depth, and villus:crypt ratio values obtained with 1.0% AmG were similar to those obtained with the positive control diet, except in the period of 21 to 28 days, when the diet with 1.0% AmG promoted higher villus:crypt ratio. The supplementation of 0.5 and 1.0% AmG affected organ weights, and reduced digestive content pH in the pylorus and in the ileum relative to the positive control diet. The dietary supplementation of 1% glutamine associated with glutamic acid improves the performance and the morphophysiology of piglets weaned at 21 days of age.